Efecto de la aplicación de cinco protectores químicos en el control de plagas y enfermedades en semillas almacenadas de Maíz (Zea mays L.) amarillo duro en Tarapoto. - Upiachihua Delgado, Payto (1997)
In order to study the effect of chemical protective protection used in the assay, mixed with insecticide in stored corn seeds (Zea mays L.) yellow hard; ie the effect they had loa protectors seed germination, protection against pests and diseases were tested. The evaluation were observed that all products used fungicídicos protective control efficiently in admixture loe insecticide to 88 days; tolclofos methyl, flutolanil + Captan and Thiabendazole in three concentrations. Captan 80% (T1) is up more than 120 days. The guards used have varied in effectiveness testing have shown that their germination where that abnormalities of seedlings is incident, diseases of seedlings, seeds without germinating; but recommended limits related ISTA normal {80% minimum). The costs are relatively low to disinfect seeds ma1z, as indicated in Annex 02; where untreated seed corn has cost $ 188.00 in relation to the treated seeds obtained cost $ 540.00; this indicating that the protection of seeds used were efficient loa.